Increased oxidative stress blood markers in well-trained rowers following two thousand-meter rowing ergometer race - Kyparos, A.; Vrabas, I. S.; Nikolaidis, M. G.; Riganas, C. S.; Kouretas, D. (The Journal of Strength and Conditioning Research, 2009)
High-intensity exercise is associated with increased oxidative stress. Rowing is very demanding requiring maintenance of high power mostly produced from aerobic metabolism. The present study aimed at investigating selective blood oxidative stress markers in response to a rowing race simulation test, consisting of 2,000 m maximal effort on a rowing ergometer, in well-trained male rowers during the preseason preparatory training period. Mean time for the 2,000-m trial was 409.4 ± 4.0 seconds, and heart rate at 2,000 m was 198 ± 1 b/min (mean ± SEM). Blood lactate concentration was 11.2 ± 0.6 mmol/L. Postexercise whole blood lysate oxidized glutathione (GSSG) concentration significantly increased (19%), whereas reduced glutathione (GSH) concentration remained unchanged, resulting in an overall decreased postexercise GSH:GSSG ratio (20%). Postexercise serum thiobarbituric acid-reactive substance concentration and protein carbonyls increased by 45 and 70%, respectively, as compared with the pre-exercise levels. Likewise, postexercise catalase activity (105%) and total antioxidant capacity (9%) significantly increased. In agreement with other studies, our data illustrate that a 2,000-m rowing ergometer race induces significant blood oxidative stress despite the rowers' high training status. In scheduling an evaluation rowing test or a competition, coaches should allow sufficient recovery time elapsed between the test and the last intensive training session. The 2,000-m rowing performance appears to be a suitable test to assess oxidative stress in rowers and could potentially serve as a model to study oxidative damage in sports science.